Electrochemical exploration of the synergistic interaction between CAU-1 and rGO for CO2 adsorption - Ibrahim, Izwaharyanie; Lim, Hong Ngee; Zulkifli, Farah Amira (Elsevier, 2023)
We report the synthesis of CAU-1 in combination with reduced graphene oxide (rGO) to create a composite material denoted as CAU-1/rGO. The synthesis involved a solvothermal process, and the resulting composite exhibited excellent structural stability and durability. To assess its interaction with CO2, the composite was purged with 99% CO2 gas in a flask. The CO2 adsorption was attributed to the favorable acid-base interaction between CO2, high oxygen contents, and the functionalized CAU-1 on the rGO scaffold, which led to a high surface-to-volume ratio. The uniform segregation of the CAU-1 within the composite contributed to its enhanced adsorption properties, as evaluated by electrochemical analysis.